Implementasi PAI Melalui Kearifan Lokal sebagai Upaya Mengatasi Kecanduan Smart Phone Anak: Study Permainan Engklek di SDN Patahunan 01 Bogor - Rizki Ahmad Fauzan; Gunawan Ikhtiono; Indriya Indriya (LPPM Institut Nasional Laa Roiba Bogor, 2023)
In the current era of digitalization, both children, teenagers, and adults are addicted to smart phones. The impact of smartphone addiction is divided into two, one positive impact and the second negative impact. The biggest impact of smartphone addiction is experienced by school children in elementary, middle, and high schools. Where children become lazy, eyes are damaged, and attitudes towards teachers and parents are not polite. This study aims to find out